1986
DOI: 10.1111/j.1600-0765.1986.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction of human neutrophils with plaque spirochetes

Abstract: Polymorphonuclear leukocytes (PMNs) encounter spirochetes in the diseased gingival crevice. The purpose of this investigation was to learn more about the nature and potential consequences of in vitro PMN‐spirochete interactions. Isolated spirochetes (various strains of Treponema denticola and T. vincentii) were incubated with human peripheral blood PMNs. PMNs were able to interact with these organisms demonstrating increased oxygen consumption, chemoluminescence, and phagocytosis. Serum was not an absolute pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…denticola [17,18,21]. Our results indicate that, in addition to with other stimulants such as Msp, this microorganism activates PMNs with dentilisin via activation of complement.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…denticola [17,18,21]. Our results indicate that, in addition to with other stimulants such as Msp, this microorganism activates PMNs with dentilisin via activation of complement.…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that T. denticola adheres to PMNs and is ingested into phagosomes [18,21]. Observations indicate that phagocytosed treponemes remain inside the phagosome, even after 60 min [21].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Human ECs were quite receptive immediately after mitosis [24,25,52] 2. Inhibition of fibroblast proliferation, lymphocyte blastogenesis, Observed in vitro, but suggests that the treponemes neutrophil degranulation, and free radical production can inhibit host reparative processes [3,4,61,62] (oral treponemal extracts) 3. Distortion of cell morphology; adhesion to fibronectin (FN);…”
Section: Arginyl/lysyl Oligopeptidasementioning
confidence: 99%
“…Many features of this bacterium are indicative of its potential to destroy host tissue and evade the host immune response. These include motility (6), the production of proteolytic enzymes (25,36), the synthesis of a factor that inhibits polymorphonuclear leukocyte function (6), and the ability to attach to host epithelial cells (16,27).…”
mentioning
confidence: 99%